(untitled) (Research, Society and Development, 2022)
The objective of the study is to measure the prevalence of self-medication for COVID-19 and associated factors among young adults during the pandemic in Brazil. This is a cross-sectional study involving young adults between the ages of 18 and 35, residing in Brazil during the COVID-19 pandemic period, conducted through online questionnaires, available through social networks. The results show that self-medication for COVID-19 was performed by 32.7% of the participants, with higher frequency in females (50.9%), people aged between 27-35 years (44.7%) and singles (57, 0%). The most used medication for self-medication was paracetamol (55.3%). The participants reported that the symptom that most led to self-medication was headache (62.5%), the main reason for self-medication was the prevention of COVID-19 (36.8%), the main motive being that they already had the medication at home (65.8%). The percentage of self-medication found was significant, increasing the chance of side effects. Therefore, health education conducts and rational use of medications are relevant measures.